Pengaruh Task Aversiveness dan Fear of Failure Terhadap Prokrastinasi Pegawai Pada Kantor Sekretariat DPRD Provinsi Sulawesi Barat - Susianti; Andi Indra Martini; Mu’fidatul Nurul Hajjad (Fakultas Ekonomi, Universitas Muslim Indonesia, 2025)
This study aims to examine the influence of task aversiveness and fear of failure on employee procrastination at the Secretariat Office of the Regional House of Representatives (DPRD) of West Sulawesi Province. Procrastination is understood as a deviation in work behavior, where employees deliberately and repeatedly postpone the completion of tasks that are actually part of their core duties and responsibilities. A quantitative approach was applied using multiple linear regression analysis, since the study involved two independent variables and one dependent variable. Data were collected through questionnaires distributed to 95 respondents, all of whom are civil servants (Aparatur Sipil Negara or ASN) at the Secretariat Office of DPRD West Sulawesi Province. The sampling technique used was total sampling. The findings reveal that task aversiveness (X1) has a significant effect on procrastination, with a t-value of 3.492 greater than the t-table value of 1.986, and a significance level of 0.001 (< 0.05). Similarly, fear of failure (X2) also shows a significant influence, with a t-value of 5.065 exceeding the t-table value of 1.986, and a significance level of 0.000 (< 0.05). These results indicate that both independent variables significantly affect employee procrastination. Moreover, the simultaneous F-test results show that the calculated F-value of 36.436 is higher than the F-table value of 3.095, with a significance level of 0.000 (< 0.05). This confirms that the regression model used is suitable for explaining employee procrastination at the Secretariat Office of DPRD West Sulawesi Province.